Problems in teaching and learning of past tenses in Portuguese language – the case of Polish students - Drzazgowska, Joanna (BELT - Brazilian English Language Teaching Journal, 2019)
The aim of this paper is to demonstrate certain problems occurring in teaching and learning past tenses in Portuguese by Polish students. The study will present primarily some questions related to the category of tense and category of aspect in the Polish and Portuguese languages. The basic differences between both systems, which make the acquisition of the Portuguese past tenses by Polish students difficult, will also be underlined. At the same time, the analysis of some of the grammars and books for learning Portuguese as Foreign Language will be conducted. The aim of the analysis will be to verify if the material regarding the past tenses allows the students to systematize their knowledge on the topic.